Reliability of urine multistix and Gram stain in the detection of asymptomatic Bacteriuria in pregnancy (2010)
BACKGROUND: Urinary tract infection is a common problem during pregnancy. Asymptomatic bacteriuria can cause the development of serious complications affecting both the mother and foetus. Urine culture, the traditional screening test is relatively expensive, time consuming and requires a microbiology laboratory and trained staff. However simpler, less expensive tests which include urine multistix and urine gramstain better suited for developing countries are available. OBJECTIVE: To determine the sensitivity, specificity and predictive values of multistix nitrite, leucocyte esterase (LE) and urine gram staining for asymptomatic bacteriuria in pregnancy. METHODS: A cross-sectional study was carried out from 1st July to 31st October 2007, at the University of Ilorin Teaching Hospital (UITH) on 125 consenting asymptomatic pregnant women. A structured proforma was used to collect information from the women and a midstream urine specimen collected in two sterile bottles. One was tested with Multistix for the presence of nitrite and leucocyte esterase and the other for bacteriological culture and urine gram stain. RESULTS: Using the gold standard of urine culture, the sensitivities of Multistix nitrite and leucocyte esterase were each 14% and the specificity 100% and 96% respectively. Urine gram stain had a sensitivity of 98% and a specificity of 74.7%. CONCLUSION: Multistix"" nitrite and leucocyte esterase are not sufficiently sensitive to be used as a screening tool for asymptomatic bacteriuria. Urine gram stain can be used in areas where facilities are inadequate for culture but cannot replace it. More studies are required to determine the accuracy of urine gram-stain.